OrCAD vs Matlab Simulink in teaching power electronics - Darwish, Mohamed K.; Alamri, Basem R.; Marouchos, Christos (My University, 2015)
The use of simulation packages in teaching power electronics plays vital part in enhancing the understanding of converter topologies. Also it plays major part in evaluating some specific characteristics like switching losses and it can also be used in the verification of some new topologies or in the optimization of some parameters. In this paper a comparison between the two software packages (OrCAD and Matlab Simulink) is presented with the focus on the main advantages and disadvantages in using both packages in teaching power electronics for undergraduate and postgraduate courses. A UPS system has been taken as a case study for both packages as it contains several power electronic converters and it is an ideal application for teaching power electronics.
Keywords: Education in power electronics; OrCAD; Power electronics; PSPICE Matlab Simulink Simulation; Simulation in Power Electronics; UPS